Modern Sensing Technologies - Mukhopadhyay, Subhas Chandra; Jayasundera, Krishanthi P.; Postolache, Octavian Adrian (Smart Sensors, Measurement and Instrumentation, 2019)
This book provides an overview of modern sensing technologies and reflects the remarkable advances that have been made in the field of intelligent and smart sensors, environmental monitoring, health monitoring, and many other sensing and monitoring contexts in today's world. It addresses a broad range of aspects, from human health monitoring to the monitoring of environmental conditions, from wireless sensor networks and the Internet of Things to structural health monitoring. Given its breadth of scope, the book will benefit researchers, practitioners, technologists and graduate students involved in the monitoring of systems within the human body, functions and activities, healthcare technologies and services, the environment, etc. .